2006
DOI: 10.1002/dvdy.20734
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the dlx gene family during formation of the cranial bones in the zebrafish (Danio rerio): Differential involvement in the visceral skeleton and braincase

Abstract: We have used dlx genes to test the hypothesis of a separate developmental program for dermal and cartilage bones within the neuro-and splanchnocranium by comparing expression patterns of all eight dlx genes during cranial bone formation in zebrafish from 1 day postfertilization (dPF) to 15 dPF. dlx genes are expressed in the visceral skeleton but not during the formation of dermal or cartilage bones of the braincase. The spatiotemporal expression pattern of all the members of the dlx gene family, support the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 73 publications
1
29
1
Order By: Relevance
“…All arch expression of dlx2a is ventral to the neurocranium (see Fig. S2 in the supplementary material), consistent with previous findings (Verreijdt et al, 2006). dlx5a is expressed within cartilages in the Meckel's-palatoquadrate and the hyosymplectic-ceratohyal joint regions at 60 hpf.…”
Section: Early Arch Expression Domains Map Onto the Developing Skeletonsupporting
confidence: 91%
“…All arch expression of dlx2a is ventral to the neurocranium (see Fig. S2 in the supplementary material), consistent with previous findings (Verreijdt et al, 2006). dlx5a is expressed within cartilages in the Meckel's-palatoquadrate and the hyosymplectic-ceratohyal joint regions at 60 hpf.…”
Section: Early Arch Expression Domains Map Onto the Developing Skeletonsupporting
confidence: 91%
“…This search was to investigate whether the dlx2b:GFP reporter construct may be missing a repressor that normally turns off dlx2b expression orally or whether in situ studies failed to detect an endogenous oral domain of dlx2b. We examined larvae at Ϸ12-h intervals from 72 to 144 hpf, and while expression was found laterally in jaw mesenchyme in what may represent dlx2b expression in developing bone (30), there was no expression in epithelium where teeth would be expected to develop (data not shown). This finding suggests that the dlx2b:GFP reporter recapitulates the endogenous zebrafish expression pattern of dlx2b in pharyngeal tooth germs and its absence from oral epithelium.…”
Section: The Zebrafish Dlx2b: Gfp Reporter Drives Expression In Zebramentioning
confidence: 99%
“…As in mammals, zebrafish ossify by achondral, perichondral and endochondral route (Cubbage and Mabee, 1996;Verreijdt et al, 2006). Markers of osteoblast and chondrocyte differentiation are conserved during zebrafish bone formation (Li et al, 2009;Yan et al, 2002) and mutations that accurately model several human diseases have been identified (Clement et al, 2008;Fisher et al, 2003;Lang et al, 2006).…”
Section: Introductionmentioning
confidence: 96%